Nanoparticles antibiotic delivery system: an alternative treatment protocol for Caseous lymphadenitis - Idris, S. B.; Arifah, A.K. (Federal University Dutsinma, 2023)
Caseous lymphadenitis is an infectious zoonotic disease of goats with severe economic implications. A major reason why management of the disease is a problem in the small ruminant livestock industry is because Corynebacterium pseudotuberculosis forms biofilm in the host and is resistant to antibiotic drugs resulting in a chronic granulomatous condition. The use of nanoparticles as a means of direct drug delivery to this organism may provide a solution to tackling it. This review focuses on caseous lymphadenitis and the different nanoparticles for antimicrobial drug delivery